Activity of ertapenem/zidebactam (WCK 6777) against problem Enterobacterales. (16th August 2022) - Mushtaq, Shazad; Garello, Paolo; Vickers, Anna; Woodford, Neil; Livermore, David M
Abstract: Background: Secondary healthcare will remain pressured for some years, both because SARS-CoV-2 will circulate as a nosocomial pathogen, and owing to backlogs of patients awaiting delayed elective procedures. These stresses will drive the use of Outpatient Parenteral Antibiotic Therapy (OPAT), which will need to cover increasingly resistant Gram-negative opportunists. We evaluated the activity of ertapenem/zidebactam, proposed for 2 + 2 g q24h administration. Materials and methods: MICs were determined, by BSAC agar dilution, for 1632 Enterobacterales submitted to the UK national reference laboratory for investigation of antimicrobial resistance. Results: Over 90% of Escherichia coli with AmpC, ESBLs, KPC, metallo- or OXA-48 carbapenemases were inhibited by ertapenem/zidebactam 1:1 at ertapenem's current 0.5 mg/L breakpoint. For other major Enterobacterales, the proportions inhibited by ertapenem/zidebactam 1:1 at 0.5 mg/L were mostly 65% to 90% but were lower for Klebsiella pneumoniae / oxytoca with metallo- or OXA-48 β-lactamases. However, animal studies support an 8 mg/L breakpoint for ertapenem/zidebactam, based on a shortened T >MIC being needed compared with ertapenem alone. On this basis ertapenem/zidebactam would count as active against 90%–100% of isolates in all groups except K. pneumoniae / oxytoca with MBLs (±OXA-48), where MICs and percent susceptibility vary substantially even with inocula within the BSAC acceptable range. Conclusions: Ertapenem/zidebactam has a proposed once-daily regimen well suited to OPAT. Even on highly conservative breakpoint projections, it has potential against MDR E. coli, including metallo-carbapenemase producers. If trial data sustain the 8 mg/L breakpoint indicated by animal experiments, its potential will extend widely across infections due to ESBL-, AmpC- and carbapenemase-producing Enterobacterales.